Strategies to reduce cesarean deliveries: surveying Polish midwives and midwifery students on external cephalic version practices - Maisa Manasar-Dyrbuś; Anna Janik; Cecylia Jendyk; Agnieszka Drosdzol-Cop; Anna Brzęk; Rafał Stojko; Jakub Staniczek (BMC Nursing)
Abstract Objectives This study aimed to evaluate the knowledge and experiences of Polish midwives regarding the external cephalic version (ECV), as well as to examine their practices related to this procedure and the perceived barriers to its implementation. Materials and methods A cross-sectional, online survey was conducted using a 22-item questionnaire developed by the authors. The survey targeted midwives and midwifery students, collecting demographic data, professional experiences, and detailed responses about knowledge, practices, and perceptions related to ECV. Results Among 535 respondents, nearly one-third were midwifery students, and the rest were professional midwives (mainly with a master’s degree). ECV was performed in over a quarter of respondents’ workplaces, with 40% reporting personal experience with the procedure. Support for ECV in primiparas was highest among students and midwives with a master’s degree, and lowest among those with a bachelor’s. A similar pattern was observed in multiparas, with elective cesarean section more often chosen by bachelor ’s-level midwives and least by students (p < 0.001). Less experienced midwives more frequently expressed concerns about complications and emergency cesarean delivery. Cesarean section was preferred in outpatient and prenatal class settings, while ECV was favored in clinical and district hospitals. Regardless of experience, the majority recognized the need for ECV training, with the strongest support among students (90.4%, p = 0.031). Conclusions The study highlights moderate awareness and limited experience with ECV among Polish midwives. The findings emphasize the necessity of structured educational programs to improve competency and confidence in ECV, particularly in outpatient and prenatal classes. Clinical trial number Not applicable.